The Regulation 650/2012 in a nutshell: habitual residence of the deceased, exercise of judicial functions, professio iuris: purpose to the CJEU Judgement of 16th July 2020, c-80/19 - Carrillo Pozo, Luis F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The 16 July 2020 judgment answers a wide range of queries, from the very grounds on which the application of Regulation 650/2012 is based (habitual residence, international nature of the succession) to the conditions under which a choice of court and the law governing the succession can be discussed, through the transcendental concept of court. In fact, this ruling will not go down in history (either it simply reflects the doctrine of previous decisions, or it merely leaves everything to the national courts, or both together), but it has the virtue of serving as a synthesis of previous contributions.